EFL STUDENTS’ VOICES ON BLENDED LEARNING: PREFERENCES AND CHALLENGES - Soni Ariawan; Lia Astuti Muliana Ningsih; Nurul Lailatul Khusniyah; Edi Sukmojati; Sulaiman Sulaiman; Siti Zurriyatun Sholihah; Malisa Malisa; Hilwa Alfiani Fitri; Zainal Abidin (Journal of English Education Forum (JEEF), 2023)
The objective of the present research was to know how EFL students perceive blended learning by using LMS with Moodle in speaking class at State Islamic University of Mataram especially in English Language Education Study Program. This research employed mixed method by involving 94 students as the respondents to fill out the questionnaires ítems and were invited to the interview. It is found that students positively perceive the use of blended Learning using LMS in speaking class. Most of the students chose to “agree” and “neutral” on their responses to the questions. Furthermore, through the interview, they mostly view LMS positively. It means that Learning speaking with blended learning using LMS had a good impact on them in learning process. Therefore, Blended Learning can be an alternative way in managing a learning process, especially during online learning. Challenges experienced by the students were also discussed in this study.